Causal Factors of Digital Marketing Affecting Business Performance of Small and Medium Businesses in The Upper Northern Region - Raungdessuwon, Satchuset; U-on, Vichit (Rajapark Journal, 2024)
This study aims to investigate the causal factors of the impact of digital marketing on the operational efficiency of small and medium-sized enterprises in northern provinces. The informant consists of five senior and middle-level managers. The results were analyzed through in-depth interviews to identify the relevant variables. A population sample of 420 individuals was surveyed using a questionnaire that included five estimated scales. Basic data were analyzed using measures such as the mean, standard deviation, popularity, correlation coefficient analysis, confirmatory factor analysis, and model suitability evaluation. The analysis was conducted using SPSS software. Data analysis revealed that digital marketing factors significantly impact the operational efficiency of small and medium-sized enterprises (SMEs) in the northern provinces. These factors include executive support, corporate culture, corporate logistics, corporate technical skills, and the success of digital marketing initiatives. The study found that these variables affect the operational efficiency of SMEs in the upper northern provinces by 0.57%, 0.55%, 0.60%, 0.62%, and 0.70%, respectively. Digital marketing plays a crucial role in expanding businesses and connecting with customers. It utilizes various tools such as Facebook, Google, Shopee, and Lazada, along with search engine optimization (SEO) to enhance visibility on online platforms.